2014
DOI: 10.1126/science.1250220
|View full text |Cite
|
Sign up to set email alerts
|

Screening for noise in gene expression identifies drug synergies

Abstract: Stochastic fluctuations are inherent to gene expression and can drive cell-fate specification. We used such fluctuations to modulate reactivation of HIV from latency—a quiescent state that is a major barrier to an HIV cure. By screening a diverse library of bioactive small molecules, we identified over 80 compounds that modulated HIV gene-expression fluctuations (i.e. ‘noise’), without changing mean expression. These noise-modulating compounds would be neglected in conventional screens and strikingly they syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
302
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(329 citation statements)
references
References 49 publications
24
302
2
1
Order By: Relevance
“…Cold Spring Harbor Laboratory Press on May 11, 2018 -Published by genome.cshlp.org Downloaded from promising example in HIV treatment with drugs that modulate expression noise (Dar et al 2014), our results suggest that similar approaches may be meaningful in cancer.…”
Section: Wwwgenomeorgmentioning
confidence: 66%
See 1 more Smart Citation
“…Cold Spring Harbor Laboratory Press on May 11, 2018 -Published by genome.cshlp.org Downloaded from promising example in HIV treatment with drugs that modulate expression noise (Dar et al 2014), our results suggest that similar approaches may be meaningful in cancer.…”
Section: Wwwgenomeorgmentioning
confidence: 66%
“…Since cell-to-cell variability in gene expression underlies important phenotypic phenomena such as persistence (Balaban et al 2004), competence (Maamar et al 2007), latency (Dar et al 2014), metastasis (Lee et al 2014), responsiveness to fluctuating environments (Acar et al 2005(Acar et al , 2008Blake et al 2006;Kaufmann et al 2007;Levy et al 2012;Vardi et al 2013), and triggering of meiosis (Nachman et al 2007), our results suggest that the probability and efficiency of these processes will be tightly coupled to environmental conditions, with potential evolutionary implications. Gene expression noise is higher at lower growth rates.…”
mentioning
confidence: 90%
“…For example, some compounds subvert variability in HIV populations. 18 . In M. tuberculosis , targeting LamA could lead to synergistic therapies that shorten treatment duration and increase the rate of cure.…”
Section: Main Textmentioning
confidence: 99%
“…This principle was illustrated in a recent study that screened for compounds altering the expression noise of the HIV LTR promoter; the authors found that, in combination with T-cell-activating compounds, noiseenhancing compounds could successfully reactivate HIV in up to 50% of resting T cells (Dar et al, 2014).…”
Section: Intercellular Heterogeneity As a Key Challenge In Medicinementioning
confidence: 99%